SUPERVISION OF VILLAGE FINANCIAL MANAGEMENT IN BANTARKAWUNG DISTRICT, BREBES REGENCY - Agus Prasetyo; Imawan Sugiharto; Moh.Taufik (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Subdistrict Head (Camat) holds a strategic role and position as a regional government apparatus responsible for exercising general governmental authority as well as providing guidance and supervision over the implementation of village governance within the subdistrict's jurisdiction. The Camat coordinates the administration of government, development, and community affairs. These responsibilities encompass various aspects, one of which is village financial management, which has become a significant issue in regional governance. In Bantarkawung District, Brebes Regency, for example, administrative problems in village financial management still persist, including delays in reporting, errors in budget recording, and weak technical guidance from the subdistrict administration. This study aims to examine the legal basis and the implementation of the Camat's authority in Bantarkawung District, Brebes Regency, as well as to identify the obstacles encountered and the efforts undertaken to optimize the role of the Camat in the guidance and supervision of village financial management. This research employs a normative juridical legal research method, focusing on regulations related to the supervision of village financial management using qualitative analysis. This study is also expected to provide input for policymakers, regional governments, and supervisory institutions in developing a guidance and supervision system that is more effective, efficient, and equitable. Keywords: Guidance and Supervision, Role of the Camat, Village Finance